Efficient lithium battery negative electrode dry slurry mixing process

By using Fe3O4/C-Si graphene composite material and appropriate process steps in the lithium battery negative electrode dry slurry process, the problems of uneven dispersion, binder failure and fineness in the lithium battery negative electrode process are solved, and the problem of uneven dispersion, failure of binder and fineness is achieved. The efficient lithium battery negative slurry combination process improves the electrical performance and production efficiency of the battery.

CN119480877APending Publication Date: 2025-02-18GUOKE ENERGY TECH INNOVATION CENT (HEFEI) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411681055.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing lithium battery negative electrode dry slurry combination process has problems such as uneven dispersion of active substances, easy failure of binder, and high slurry fineness.

Method used

Fe3O4/C-Si graphene composite material is used as the negative electrode active material, and powder mixing, deionized water is added and binder is uniformly stirred to form a negative electrode slurry with low fineness and good dispersion.

Benefits of technology

It improves the rate performance and circulation performance of lithium batteries, simplifies process steps, shortens the slurry time, improves production efficiency, and solves the problems of binder failure and high slurry fineness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119480877A_ABST
    Figure CN119480877A_ABST
Patent Text Reader

Abstract

The invention discloses an efficient lithium battery negative electrode dry slurry mixing process, and relates to the technical field of lithium ion batteries. The preparation method at least comprises the following steps: adding a Fe3O4 / C-Si graphene composite material, a thickening agent and a conductive agent into a slurry mixing tank, and stirring and dispersing for the first time to obtain mixed dry powder; adding deionized water into the mixed dry powder at least twice, and stirring and dispersing for the second time to obtain pre-mixed slurry; adding a binder and an anti-cracking agent into the pre-mixed slurry, and stirring and dispersing for the third time to obtain uniformly mixed negative electrode slurry; and sieving and discharging the negative electrode slurry. According to the invention, the Fe3O4 / C-Si graphene composite material is selected as a negative electrode active material, so that the electrical property of the lithium battery is improved, and the production efficiency is effectively improved in cooperation with a dry slurry mixing process provided by the invention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to an efficient dry slurrying process for negative electrodes of lithium batteries. Background Art

[0002] Slurry mixing is the most important link in the entire production process of lithium-ion batteries. The slurry mixing process can affect the quality of lithium-ion battery products by up to 30%. The battery slurry mixing process is to evenly disperse the active material, binder, conductive agent, thickener, etc. in a solvent according to a certain formula ratio to make a slurry for coating. The mixing and dispersion of slurry is very important in the production of lithium-ion batteries. The quality of slurry dispersion directly affects the quality of subsequent lithium-ion battery production and the performance of its products.

[0003] According to the different powder mixing order, the battery slurry mixing process can be roughly divided into two types: wet and dry. The difference between wet slurry mixing and dry slurry mixing process is mainly reflected in the different solid content of slurry at different stages. The wet slurry mixing process is widely used in the preparation of lithium-ion battery slurry in China. The process characteristics are to first prepare a well-dispersed conductive glue, and then mix and disperse the active substance and the conductive glue. The wet slurry has good fluidity and fewer bubbles. However, the wet process is not only time-consuming, but also has a cumbersome order of adding materials. The slurry mixing effect is poor for systems with a tendency to agglomerate and poor wettability.

[0004] The traditional dry slurry mixing process first premixes the active material, conductive agent and other powder materials in a slurry mixer. After premixing, a binder is added for mixing and dispersion, and finally a certain amount of solvent is added to dilute and adjust the viscosity of the slurry. However, this method has many disadvantages: (1) The viscosity adjustment time is long, and the solid content is affected during the viscosity adjustment process, making it difficult to obtain the target solid content; (2) It is easy to cause poor slurry dispersion; (3) The binder is easily ineffective after being added too early under long-term stirring; (4) The prepared slurry has a large fineness, which affects the subsequent coating effect and battery performance. Therefore, it is urgent to provide an efficient dry slurry mixing process for lithium battery negative electrodes that can improve production efficiency while ensuring the electrical performance of lithium batteries. Summary of the invention

[0005] The purpose of the present invention is to provide an efficient dry slurry process for lithium battery negative electrode to solve the following technical problems: The existing dry slurry mixing process for negative electrodes of lithium batteries has problems such as uneven dispersion of active materials, easy failure of binders and high slurry fineness.

[0006] The purpose of the present invention can be achieved through the following technical solutions: An efficient dry slurrying process for lithium battery negative electrode comprises at least the following steps: Adding the Fe3O4 / C-Si graphene composite material, thickener and conductive agent into a slurry mixing tank, performing a first stirring and dispersion, and obtaining a mixed dry powder; Adding deionized water to the mixed dry powder at least twice, stirring and dispersing for a second time to obtain a pre-mixed slurry; Adding a binder and an anti-cracking agent to the pre-mixed slurry, stirring and dispersing for a third time to obtain a uniformly mixed negative electrode slurry; The negative electrode slurry is sieved out.

[0007] As a further solution of the present invention: the preparation method of the Fe3O4 / C-Si graphene composite material comprises at least the following steps: Dissolve ferrocene in toluene, stir and dissolve it in a N2 atmosphere, add graphene, and disperse it by ultrasonic for 20-60 minutes, then add silicone oil, stir and disperse it evenly, and finally add oleic acid, stir and react evenly for 8-20 hours under oil bath heating conditions to obtain a precursor; The precursor is placed in an iron crucible, wrapped with tin foil and placed in a tubular furnace. Under an atmosphere of H2 / Ar mixed gas, the temperature is increased to 500-600°C at a rate of 1-2°C / min, then the temperature is kept constant for activation for 1-2h, and the temperature is naturally cooled to room temperature to obtain the Fe3O4 / C-Si graphene composite material.

[0008] As a further solution of the present invention: the solid content of the negative electrode slurry is 49-51%, the content of the anti-cracking agent is 0.1-0.2%, the viscosity of the negative electrode slurry is 8000-9000 mPa·s, and the fineness of the negative electrode slurry is less than 15 μm.

[0009] As a further solution of the present invention: the mass ratio of the Fe3O4 / C-Si graphene composite material, the thickener and the conductive agent is 94-97:1-2:1-2:2-4.

[0010] As a further solution of the present invention: the mixed dry powder forming the pre-slurry comprises at least the following steps: Add deionized water accounting for at least 50% of the total weight of deionized water to the mixed dry powder for pre-stirring at a stirring speed of 20-55 r / min and a dispersion speed of 300-500 r / min, scrape the material every 15 minutes to observe the slurry state, and obtain the first pre-mixed slurry after 20-40 minutes; The remaining deionized water is added to the first pre-mixed slurry and stirred at a high speed of 25-55 r / min, a dispersion speed of 1300-1500 r / min, a vacuum of ≤-90 kPa, and the material is scraped every 15 minutes to obtain the pre-mixed slurry after 80-120 minutes.

[0011] As a further solution of the present invention: the revolution speed of the first stirring and dispersing is 20-50 r / min, and the dispersing speed is 300-500 r / min; The revolution speed of the third stirring and dispersing is 25-50 r / min, and the dispersing speed is 300-600 r / min.

[0012] As a further solution of the present invention: the thickener is carboxymethyl cellulose, and the conductive agent is one or a mixture of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, metal powder or carbon fiber.

[0013] As a further solution of the present invention: the binder is styrene-butadiene rubber, and the anti-cracking agent is at least one of ethylene glycol, propylene glycol, glycerol, isopropanol, butanol, 1,2-butanediol or 1,3-butanediol.

[0014] Beneficial effects of the present invention: (1) The present invention prepares Fe3O4 / C-Si nanoparticle composite materials as negative electrode active materials. In combination with the negative electrode dry slurrying process provided by the present invention, the prepared negative electrode slurry has small fineness and the prepared Fe3O4 / C-Si nanoparticle composite materials are evenly dispersed, which greatly improves the rate performance and cycle performance of the lithium battery. In addition, the slurrying process is simple to operate, thereby improving production efficiency.

[0015] The negative electrode dry slurry process provided by the present invention is to dry mix the powders of the negative electrode active material, thickener and conductive agent, add deionized water to knead and stir, and finally add a binder and an anti-cracking agent to prepare the negative electrode slurry after uniform stirring. Deionized water is added at least twice, and part of the deionized water is added for pre-stirring for the first time, and then the remaining deionized water is added for high-speed stirring, and finally the binder and the anti-cracking agent are added. The slurry process of the present invention effectively solves the particle problem of soft agglomerated materials such as negative electrode active materials, and a slurry with a higher solid content can be prepared at the same viscosity. The prepared slurry has a small fineness, which improves the electrical performance of the battery. The binder is added at the end to avoid the binder from failing under long-term stirring. The negative electrode dry slurry process provided by the present invention not only has simple process steps, but also omits the viscosity adjustment step to greatly improve production efficiency, and there is no particle agglomeration problem during the operation. The prepared slurry has a small fineness and good dispersibility, and can obtain the target solid content and viscosity, which can effectively solve the particle problem of soft agglomerated materials. Compared with the wet process, the negative electrode dry slurry mixing process provided by the present invention is simple to operate, greatly shortens the slurry mixing time, and improves production efficiency; compared with similar dry slurry mixing, the slurry mixing can be completed in four steps, which simplifies the production steps and has high production efficiency.

[0016] The present invention uses oleic acid, ferrocene, silicone oil and graphene as raw materials, and finally obtains a graphene-loaded Fe3O4 / C-Si nanoparticle composite material with a unique carbon-silicon coating structure through low-temperature carbonization. The composite material wraps Fe3O4 nanoparticles in a carbon-silicon shell of uniform thickness, and is embedded in a graphene sheet at the same time. Due to the unique structure of the composite material, not only the electrical conductivity of the material is greatly enhanced, but also the structural stability is enhanced, and its electrochemical performance is improved. While forming Fe3O4 nanoparticles during the carbonization process, a carbon-silicon-coated structure is also formed. By coating the carbon-silicon shell of uniform thickness on the outside of the Fe3O4 nanoparticles, not only the disadvantage of poor electrical conductivity of ferroferric oxide is effectively improved, but also the electrical conductivity of the material as a whole is improved, the rapid transfer of lithium ions and charges is guaranteed, and the rate performance of the battery is improved. The presence of the carbon-silicon shell can effectively prevent the phenomenon of agglomeration of Fe3O4 nanoparticles during the charge and discharge process, thereby improving the cycle stability. At the same time, the violent volume expansion phenomenon during the reaction process is also weakened, the stability of the electrode material structure is maintained, and the cycle stability performance of the material is guaranteed. At the same time, due to the introduction of graphene materials, in conjunction with the negative electrode dry slurry process provided by the present invention, the agglomeration of Fe3O4 is greatly reduced, thereby having a better dispersion effect, which is beneficial to the electron transfer process, improves the conductivity of the overall material, and thus reduces the charge transfer resistance of the composite electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0018] Figure 1 The figure is a flow chart of the preparation of the dry slurry process for the negative electrode of a lithium battery in one embodiment. DETAILED DESCRIPTION

[0019] The following will be described clearly and completely in conjunction with the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] Example 1 The preparation method of Fe3O4 / C-Si graphene composite material comprises the following steps: 1.5 g of ferrocene was dissolved in 30 ml of toluene, and magnetically stirred for 1 h under N2 atmosphere. After sufficient stirring and dissolution, 1 g of graphene was added, stirred for 30 min, and then ultrasonically dispersed for 30 min. Then 30 ml of silicone oil was added, and stirred and dispersed evenly. Finally, 6 g of oleic acid was added and stirred and reacted evenly under 65 ° C oil bath heating conditions for 12 h to obtain a precursor of a composite material. The precursor obtained after the above reaction was placed in an iron crucible, wrapped with tin foil and placed in a tubular furnace. Under the atmosphere of H2 / Ar mixed gas (hydrogen accounts for 5%), the temperature was increased to 550°C at a rate of 2°C / min and then activated at a constant temperature for 1 hour. After naturally cooling to room temperature, carbon-silicon-coated nano-Fe3O4 supported on graphene was obtained, namely, Fe3O4 / C-Si graphene composite material.

[0021] See also Figure 1 The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1000g of Fe3O4 / C-Si graphene composite material and add it to the mixing tank, then add 12g of carboxymethyl cellulose powder and 12g of conductive graphite in sequence. Close the mixing tank, start stirring at 30 r / min, and disperse at 400 r / min to mix the mixed dry powder. After 15 min, open it to observe the state of the solid powder, and continue stirring to obtain a mixed dry powder; Weigh 1000g of deionized water and add it to the above mixed dry powder for pre-stirring. Turn on the stirring speed of 40r / min, disperse at 400r / min for stirring and kneading. Scrape the material every 15min to observe the slurry state. After 20min, open the slurry tank to obtain the first pre-slurry. Weigh 1000g of deionized water again and add it to the first pre-mixed slurry for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain the pre-mixed slurry after 90min. Weigh 40g of styrene-butadiene rubber and 2g of 1,3-butanediol and add them to the pre-mixed slurry. Stir at 40r / min, disperse at 400r / min, set vacuum ≤-90kPa, scrape once every 15min, and obtain a uniformly mixed negative electrode slurry after 30min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0022] Example 2 The preparation method of Fe3O4 / C-Si graphene composite material comprises the following steps: 2g of ferrocene was dissolved in 30ml of toluene, and magnetically stirred for 1h under N2 atmosphere. After sufficient stirring and dissolution, 1g of graphene was added, stirred for 30min, and then ultrasonically dispersed for 30min. Then 30ml of silicone oil was added, and stirred and dispersed evenly. Finally, 6g of oleic acid was added and stirred and reacted evenly for 12h under 65℃ oil bath heating conditions to obtain a precursor of a composite material. The precursor obtained after the above reaction was placed in an iron crucible, wrapped with tin foil and placed in a tubular furnace. Under the atmosphere of H2 / Ar mixed gas (hydrogen accounts for 5%), the temperature was increased to 550°C at a rate of 2°C / min and then activated at a constant temperature for 1 hour. After naturally cooling to room temperature, carbon-silicon-coated nano-Fe3O4 supported on graphene was obtained, namely, Fe3O4 / C-Si graphene composite material.

[0023] The components and slurry mixing process of the negative electrode slurry are the same as those in Example 1.

[0024] Example 3 The preparation method of Fe3O4 / C-Si graphene composite material comprises the following steps: Dissolve 1g of ferrocene in 30ml of toluene and stir magnetically for 1h under N2 atmosphere. After sufficient stirring and dissolving, add 1g of graphene, stir for 30min, and then ultrasonically disperse for 30min. Then add 30ml of silicone oil and stir and disperse evenly. Finally, add 4g of oleic acid and stir and react evenly for 12h under 65℃ oil bath heating conditions to obtain a precursor of a composite material. The precursor obtained after the above reaction was placed in an iron crucible, wrapped with tin foil and placed in a tubular furnace. Under the atmosphere of H2 / Ar mixed gas (hydrogen accounts for 5%), the temperature was increased to 550°C at a rate of 2°C / min and then activated at a constant temperature for 1 hour. After naturally cooling to room temperature, carbon-silicon-coated nano-Fe3O4 supported on graphene was obtained, namely, Fe3O4 / C-Si graphene composite material.

[0025] The components and slurry mixing process of the negative electrode slurry are the same as those in Example 1.

[0026] Example 4 The components and preparation method of the Fe3O4 / C-Si graphene composite material are the same as those in Example 1.

[0027] See also Figure 1 The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1000g of Fe3O4 / C-Si graphene composite material and add it to the mixing tank, then add 15g of carboxymethyl cellulose powder and 15g of conductive graphite in sequence. Close the mixing tank, start stirring at 40 r / min, and disperse at 400 r / min to mix the mixed dry powder. After 15 min, open it to observe the state of the solid powder, and continue stirring to obtain a mixed dry powder; Weigh 1000g of deionized water and add it to the above mixed dry powder for pre-stirring. Turn on the stirring speed of 40r / min, disperse at 400r / min for stirring and kneading. Scrape the material every 15min to observe the slurry state. After 20min, open the slurry tank to obtain the first pre-slurry. Weigh 1000g of deionized water again and add it to the first pre-mixed slurry for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain the pre-mixed slurry after 90min. Weigh 40g of styrene-butadiene rubber and 3g of 1,3-butanediol and add them to the pre-mixed slurry. Stir at 40r / min, disperse at 400r / min, set vacuum ≤-90kPa, scrape the material every 15min, and obtain a uniformly mixed negative electrode slurry after 30min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0028] Example 5 The components and preparation method of the Fe3O4 / C-Si graphene composite material are the same as those in Example 1.

[0029] See also Figure 1 The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1500g of Fe3O4 / C-Si graphene composite material and add it to the mixing tank, then add 25g of carboxymethyl cellulose powder and 25g of conductive graphite in sequence. Close the mixing tank, start stirring at 40 r / min, and disperse at 500 r / min to mix the mixed dry powder. After 15 min, open it to observe the state of the solid powder, and continue stirring to obtain a mixed dry powder; Weigh 1000g of deionized water and add it to the mixed dry powder for pre-stirring. Start stirring at 50r / min and disperse at 500r / min for stirring and kneading. Scrape the material every 15min to observe the slurry state. After 20min, open the slurry mixing tank to obtain the first pre-slurry. Weigh 2000g of deionized water again and add it to the first pre-mixed slurry for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain the pre-mixed slurry after 90min. Weigh 60g of styrene-butadiene rubber and 3g of 1,3-butanediol and add them to the pre-mixed slurry. Stir at 40r / min, disperse at 500r / min, set vacuum ≤-90kPa, scrape the material every 15min, and obtain a uniformly mixed negative electrode slurry after 30min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0030] Comparative Example 1 The preparation steps of Fe3O4 / C-Si graphene composite material are omitted.

[0031] See also Figure 1 The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1000g of graphite and add it to the mixing tank, then add 12g of carboxymethyl cellulose powder and 12g of conductive graphite in sequence. Close the mixing tank, stir at 30 r / min, disperse at 400 r / min to mix the mixed dry powder, open it to observe the state of the solid powder after 15 min, and continue stirring to obtain a mixed dry powder; Weigh 1000g of deionized water and add it to the above mixed dry powder for pre-stirring. Turn on the stirring speed of 40r / min, disperse at 400r / min for stirring and kneading. Scrape the material every 15min to observe the slurry state. After 20min, open the slurry tank to obtain the first pre-slurry. Weigh 1000g of deionized water again and add it to the first pre-mixed slurry for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain the pre-mixed slurry after 90min. Weigh 40g of styrene-butadiene rubber and 2g of 1,3-butanediol and add them to the pre-mixed slurry. Stir at 40r / min, disperse at 400r / min, set vacuum ≤-90kPa, scrape once every 15min, and obtain a uniformly mixed negative electrode slurry after 30min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0032] Comparative Example 2 The preparation steps of Fe3O4 / C-Si graphene composite material are the same as those in Example 1: The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1000g of Fe3O4 / C-Si graphene composite material and add it to the mixing tank, then add 12g of carboxymethyl cellulose powder, 12g of conductive graphite, 40g of styrene-butadiene rubber and 2g of 1,3-butanediol in sequence. Close the mixing tank, start stirring at 30 r / min, and disperse at 400 r / min to mix the mixed dry powder. After 15 min, open and observe the state of the solid powder, and continue stirring to obtain a mixed dry powder; Weigh 2000g of deionized water and add it to the above mixture for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain a uniformly mixed negative electrode slurry after 120min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0033] The components and dry slurry process of the lithium battery negative electrode slurry are the same as those of Comparative Example 2. Comparative Example 3 The preparation steps of Fe3O4 / C-Si graphene composite material are omitted.

[0034] The dry slurry process for lithium battery negative electrode includes the following steps: Weigh 1000g of graphite and add it to the mixing tank, then add 12g of carboxymethyl cellulose powder, 12g of conductive graphite, 40g of styrene-butadiene rubber and 2g of 1,3-butanediol in sequence. Close the mixing tank, stir at 30 r / min, disperse at 400 r / min to mix the mixed powder, open it to observe the state of the solid powder after 15 min, and continue stirring to obtain a mixed powder; Weigh 2000g of deionized water and add it to the above mixture for high-speed dispersion. Stir at 40r / min, disperse at 1500r / min, vacuum ≤-90kpa, scrape once every 15min, and obtain a uniformly mixed negative electrode slurry after 120min. Prepare a dry and clean 200-mesh filter screen, sieve the negative electrode slurry that meets the trial production requirements, and keep slow stirring and vacuum ≤-90kpa before discharging.

[0035] Preparation of lithium battery: a. Preparation of negative electrode sheets: The negative electrode slurry prepared in Examples 1-6 and Comparative Examples 1-3 was evenly coated on the negative electrode current collector copper foil, then dried at 85° C. and cold pressed, and then trimmed, cut, slit, and welded to the tabs to prepare the negative electrode sheets.

[0036] b. Preparation of positive electrode sheets: The positive electrode active material lithium cobalt oxide, conductive carbon black, and binder polyvinylidene fluoride are dissolved in N-methylpyrrolidone in a mass ratio of 96:2:2 and mixed evenly to form a positive electrode slurry. The positive electrode slurry is then evenly coated on the positive electrode collector aluminum foil, and then dried at 85°C, cold pressed, trimmed, cut, slit, and welded to the ears to prepare the positive electrode sheets.

[0037] c. Battery assembly: The positive electrode sheet, negative electrode sheet and isolation membrane (polypropylene microporous membrane with a thickness of 12μm) are made into a battery cell through a winding process, and then packaged with an aluminum-plastic film and injected with electrolyte. The electrolyte uses 1M LiPF6 as the lithium salt and the organic solvent uses EC / EMC=3:7 (volume ratio). After the formation, capacity, shaping and other processes, the preparation of the lithium-ion battery is completed.

[0038] Electrochemical performance testing: The fineness and viscosity of the negative electrode slurries obtained in Examples 1-5 and Comparative Examples 1-4 were tested, and the electrochemical properties of the lithium batteries obtained in Examples 1-5 and Comparative Examples 1-4 were tested. The voltage test range was 0.01-3.0 V, and the test temperature was 25° C. The test results are shown in the following table:

[0039] From the data in the above table, it can be seen that the negative electrode slurry prepared by the dry slurrying process in Examples 1-5 of the present invention has a small fineness and high viscosity, and the prepared lithium battery has excellent rate performance and cycle performance. In Comparative Example 1, graphite is added as the negative electrode active material, and the measured rate performance and cycle performance are reduced. In Comparative Example 2, after the powder is mixed once during the preparation of the negative electrode slurry, sufficient deionized water is directly added for stirring and kneading. In Comparative Example 3, the Fe3O4 / C-Si graphene composite material prepared in the present invention is added, and the negative electrode material is not added in batches for stirring and kneading. The measured slurry fineness is large, and the rate performance and cycle performance are reduced, indicating that the Fe3O4 / C-Si graphene composite material can be improved as the negative electrode active material of the lithium battery, and the slurry fineness obtained by the negative electrode dry slurrying process of the present invention is small, the negative electrode active material has good dispersibility, and the target solid content and viscosity can be obtained, which improves the electrical performance of the lithium battery.

[0040] The above is a detailed description of an embodiment of the present invention, but the content is only a preferred embodiment of the present invention and cannot be considered to limit the scope of implementation of the present invention. All equivalent changes and improvements made within the scope of the present invention should still fall within the scope of the patent coverage of the present invention.

Claims

1. An efficient dry slurrying process for lithium battery negative electrode, characterized in that: At least the following steps are included: Adding the Fe3O4 / C-Si graphene composite material, thickener and conductive agent into a slurry mixing tank, performing a first stirring and dispersion, and obtaining a mixed dry powder; Adding deionized water to the mixed dry powder at least twice, stirring and dispersing for a second time to obtain a pre-mixed slurry; Adding a binder and an anti-cracking agent to the pre-mixed slurry, stirring and dispersing for a third time, to obtain a uniformly mixed negative electrode slurry; The negative electrode slurry is sieved out.

2. The high-efficiency dry slurrying process for lithium battery negative electrode according to claim 1, characterized in that: The preparation method of the Fe3O4 / C-Si graphene composite material comprises at least the following steps: Dissolve ferrocene in toluene, stir and dissolve it in a N2 atmosphere, add graphene, and disperse it by ultrasonic for 20-60 minutes, then add silicone oil, stir and disperse it evenly, and finally add oleic acid, stir and react evenly for 8-20 hours under oil bath heating conditions to obtain a precursor; The precursor is placed in an iron crucible, wrapped with tin foil and placed in a tubular furnace. Under an atmosphere of H2 / Ar mixed gas, the temperature is increased to 500-600°C at a rate of 1-2°C / min, then the temperature is kept constant for activation for 1-2h, and the temperature is naturally cooled to room temperature to obtain the Fe3O4 / C-Si graphene composite material.

3. The efficient dry slurrying process for lithium battery negative electrode according to claim 1, characterized in that: The solid content of the negative electrode slurry is 49-51%, the content of the anti-cracking agent is 0.1-0.2%, the viscosity of the negative electrode slurry is 8000-9000 mPa·s, and the fineness of the negative electrode slurry is less than 15 μm.

4. The high-efficiency dry slurrying process for negative electrode of lithium battery according to claim 1, characterized in that: The mass ratio of the Fe3O4 / C-Si graphene composite material, the thickener and the conductive agent is 94-97:1-2:1-2:2-4.

5. The high-efficiency dry slurrying process for negative electrode of lithium battery according to claim 1, characterized in that: The mixed dry powder to form the pre-slurry comprises at least the following steps: Add deionized water accounting for at least 50% of the total weight of deionized water to the mixed dry powder for pre-stirring at a stirring speed of 20-55 r / min and a dispersion speed of 300-500 r / min, scrape the material every 15 minutes to observe the slurry state, and obtain the first pre-mixed slurry after 20-40 minutes; The remaining deionized water is added to the first pre-mixed slurry and stirred at a high speed of 25-55 r / min, a dispersion speed of 1300-1500 r / min, a vacuum of ≤-90 kPa, and the material is scraped once every 15 minutes. After 80-120 minutes, the pre-mixed slurry is obtained.

6. The efficient dry slurrying process for lithium battery negative electrode according to claim 1, characterized in that: The revolution speed of the first stirring and dispersing is 20-50 r / min, and the dispersing speed is 300-500 r / min; The revolution speed of the third stirring and dispersing is 25-50 r / min, and the dispersing speed is 300-600 r / min.

7. The efficient dry slurrying process for lithium battery negative electrode according to claim 1, characterized in that: The thickener is carboxymethyl cellulose, and the conductive agent is one or a mixture of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, graphene, metal powder or carbon fiber.

8. The efficient dry slurrying process for lithium battery negative electrode according to claim 1, characterized in that: The adhesive is styrene-butadiene rubber, and the anti-cracking agent is at least one of ethylene glycol, propylene glycol, glycerol, isopropanol, butanol, 1,2-butanediol or 1,3-butanediol.